Covid-19 fully exposes Zimbabwe’s comatose economy - Tapiwa Chagonda (The Thinker)
The Covid-19 pandemic has left Zimbabwe in an extremely difficult catch-22 situation. Given the nation’s parlous health system, conventional wisdom would suggest that the country should go into a total lockdown in a bid to contain the spread of the virus.